Empirisch-konstruktive Bestimmung des Begriffs „Lehr-Lern-Labor“ und seine konzeptionelle Einordnung in vergleichbare Organisationsformen der Lehramtsausbildung in MINT-Fächern (mathematica didactica, 2020)
The great potential of Teaching-Learning-Labs (TLL) in MINT-subjects to foster the development of professional competences of future teachers is beyond dispute in mathematics education and related disciplines such as educational sciences. There is a broad consensus that TLL in MINT-subjects connect the theoretical education of teachers with reflective practice by enabling diverse interactions with pupils. However, a universally accepted definition of this special concept in teacher education in MINT-subjects is still missing. In order to promote deepening discussions a definition of TLL based on empirical studies will be presented. Furthermore, conceptional differences to comparable concepts will be discussed.